ETNOMATEMATIKA: EKSPLORASI KONSEP GEOMETRI TRANSFORMASI PADA KAIN TENUN LUNGGI SAMBAS - Uray Tantri Ainiyyah; Ressy Rustanuarsi (Universitas Muhammadiyah Lampung, 2025)
The connection between mathematics and local culture is often underutilized in education, even though cultural elements can serve as rich contextual resources for understanding mathematical concepts. This study aims to identify the concepts of geometric transformations embedded in the Pucuk Rebung motif of Lunggi Sambas woven fabric. The research employs a qualitative approach with an exploratory design. The researcher acted as the key instrument in this study, and data were collected through observation, documentation, and literature review. Data analysis techniques included data collection, data condensation, data presentation, and conclusion drawing. The findings reveal that the Pucuk Rebung motif in Lunggi Sambas woven fabric contains geometric transformation concepts, such as reflection, translation, and rotation. Therefore, Lunggi Sambas woven fabric can be integrated into the learning process to enhance meaningful learning and serve as a resource for teaching mathematics, particularly in the topic of geometric transformations.